Appreciative Inquiry and Boot Camp Translation: Combining Methods for Community Health Improvement - John M Westfall; Linda Zittleman; Maret Felzien; Jodi Summers Holtrop; Tristen Hall; Mary Fisher; Matt Simpson; Griselda Pena-Jackson; Donald Nease, Jr. (Journal of Participatory Research Methods)
Communities are dealing with persistent health problems, despite the enormous investment in health research, service delivery, and program development to address those health concerns. While there may be an evidence base for addressing some community health concerns, too often there is incomplete or no medical evidence for addressing many concerns. The High Plains Research Network and Colorado Research Network have used an appreciative inquiry approach to their work for several years, identifying positive aspects of care and developing programs to replicate what is working. Based on five years of informal appreciative-inquiry research and five formal appreciative inquiry projects, we have developed a standard process and method for conducting appreciative-inquiry guided Boot Camp Translations. The purpose of this methodology manuscript is to describe the general approach of using appreciative inquiry as a research tool and the standard process for conducting appreciative inquiry as a patient engagement tool to identify local evidence and develop local solutions.